Synthesis of Pyrano[2,3-b]indol-4-ones Fused with Medium-Sized Rings: A Base-Induced C–C σ-Bond Insertion and Subsequent I2-Mediated 1,2-Acyl Migration/Cyclization Reaction - Wang, Yan; Wang, Zongkang; Fei, Nana; He, Peng; Kong, Lingkai; Li, Yanzhong (Synlett, 2025)
A novel tandem reaction starting from alkynones and cyclic ketones has been developed to efficiently synthesize pyranoindolones fused with a medium-sized ring. This process involves a base-induced C–C σ-bond cleavage reaction of cyclic ketone and subsequent I2-mediated 1,2-acyl migration/cyclization reaction. Transition-metal-free and easily accessible starting materials make this 1,2-acyl migration/cyclization methodology attractive.
Keywords: C–C σ-bond cleavage; 1,2-acyl migration/cyclization; transition-metal-free; mild reaction conditions; one-pot synthesis